2019
DOI: 10.7202/1065214ar
|View full text |Cite
|
Sign up to set email alerts
|

La pénurie de professeures de sciences infirmières au Canada et ses effets sur les programmes de formation en sciences infirmières offerts en français

Abstract: Cette étude qualitative décrit la pénurie de professeures en sciences infirmières et ses effets actuels et potentiels sur les programmes canadiens de formation en sciences infirmières offerts en français, ainsi que les stratégies préconisées par les directrices de ces programmes afin d’en atténuer les effets. Les effets de la pénurie sont particulièrement préoccupants dans le cas des programmes offerts dans un contexte francophone minoritaire ou en région éloignée. La pénurie mettrait en péril les programmes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…This study revealed that, not only is there a lack of pediatric oncology nurses working in a community setting, but also that precious few of them speak French. As indicated in a paper by Chartrand et al (2019), French is considered to be an optional asset when hiring new staff members, e.g., nurses to provide home-based care and services to pediatric cancer patients and their families. Other studies do indeed show that most employers prioritize clinical skills over linguistic competencies in their hiring criteria (Aucoin, 2018).…”
Section: Causesmentioning
confidence: 99%
“…This study revealed that, not only is there a lack of pediatric oncology nurses working in a community setting, but also that precious few of them speak French. As indicated in a paper by Chartrand et al (2019), French is considered to be an optional asset when hiring new staff members, e.g., nurses to provide home-based care and services to pediatric cancer patients and their families. Other studies do indeed show that most employers prioritize clinical skills over linguistic competencies in their hiring criteria (Aucoin, 2018).…”
Section: Causesmentioning
confidence: 99%
“…Par ailleurs, une étude réalisée en Nouvelle-Écosse démontre que la majorité des employeurs priorisent les compétences cliniques plutôt que les compétences linguistiques à l'embauche, ce qui réduit l'offre de services en français (N. Aucoin, 2018). Malgré cela, la difficulté de recruter des professionnels bilingues est encore plus criante dans les milieux où il est tout simplement impossible de pourvoir les postes en raison d'une pénurie de professionnels de la santé (N. Aucoin, 2018 ;Chartrand et al, 2019 ;Forgues et al, 2011).…”
Section: Professionnels De La Santé Qui Fournissent Des Soins Aux Closmunclassified